Blackness and value : seeing double - Barrett, Lindon, 1961-2008 (Cambridge studies in American literature and culture, 1999)
"Blackness and Value investigates the principles by which "value" operates and asks whether it is useful to imagine that the concepts of racial blackness and whiteness in the United States operate in terms of these principles." "The book traces several interrelations between value and race, such as literate/illiterate, the signing/singing voice, time/space, civic/criminal, and academy/street, and offers relevant and fresh readings of two novels by Ann Petry. Whereas commonly approaches to race and value are examined historically or sociologically, this intriguing study provides a new critical approach that speaks to theorists of race as well as gender and queer studies."--Jacket